Determining Optimal SVC Location for Voltage Stability Using Multi-Criteria Decision Making Based Solution: Analytic Hierarchy Process (AHP) Approach - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
Due to latest blackouts in the world, voltage instability and voltage collapse have become the main issues studied in electrical power systems. For this purpose, various Flexible AC Transmission Systems (FACTS) devices have been utilized for many years, increasing voltage stability while at the same time improving system performance, reliability, supply quality and providing environmental benefits. These devices location for enhancing voltage stability is a significant problem for actual power networks. When determining the best location of the controller, an optimal solution should be found to increase the loading margin and also reduce voltage deviation and power losses. In the literature, the weight coefficients of the criteria were chosen equally or approximate values were obtained by trial and error method and Multi-Criteria Decision Making (MCDM) techniques have never been used in finding the optimal location of FACTS devices. This article presents a novel technique for optimal location of Static Var Compensator (SVC) devices in power systems using MCDM. The simulation was conducted on Power System Analysis Toolbox (PSAT) in MATLAB. In the proposed approach, IEEE 14-bus, IEEE 30-bus and IEEE 118-bus test systems were used and the optimal location was found out with Analytic Hierarchy Process (AHP), an MCDM technique. The consistency of the results has been checked and the reliability has been increased, and the results of the application are promising. In addition, the optimal location of the SVC for different contingencies was found, and the effects of the overloaded lines and Phase-Shifting Transformer (PST) on the network were analyzed.
Keywords: Static VAr compensators; Power system stability; Stability criteria; Voltage; Reactive power; Capacitors; Indexes; Voltage stability; optimal location; FACTS; MCDM; PSAT; CONTINUATION POWER-FLOW; FACTS DEVICES; OPTIMAL PLACEMENT; SYSTEM; OPTIMIZATION; ALGORITHM; RECONFIGURATION; ALLOCATION